Effect of Different Brackish Water Depths on the Performance of a Solar Still - LABIAD, A.; SELLAMI, M. H.; CHERRAYE, R.; REHOUMA, Y. (University of Eloued جامعة الوادي, 2018)
Water is essential to life. The supply of drinking water is becoming an increasingly important issue in many areas of the world especially. In remote and arid areas in Algeria and world. Among the non-conventional methods to desalinate brackish water or sea water, is solar distillation. The present study aims to improve the solar still performance, and to increase its productivity. So it is necessary to evaluate some important parameters affecting the system productivity. The effect of water depth in the basin on the water productivity was evaluated. In the same time, Desalination process were investigated. Different depths of brackish water (1cm, 2cm and 3cm). The optimal brine water depths1cm and productivity 3530 ml/m².
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Solar still, depth water, brackish water, productivity fresh water.